Kedaruratan Kesehatan Masyarakat akibat Cacar Monyet (Mpox) - Hamsu Kadriyan (Lombok Medical Journal, 2024)
With the declaration of a public health emergency concerning Mpox (monkeypox), vigilance and mitigation measures are necessary to prevent the adverse effects of this condition. In Indonesia, 88 new cases have been reported, primarily of the Clade II variant. However, new Mpox variants, such as Clade Ia and Ib, have also been identified. This situation requires careful attention and multidisciplinary management to achieve optimal outcomes.